Efek Antibakterisid Madu terhadap Escherichia coli - Alghazali Samapta; - Sagiran (Universitas Muhammadiyah Yogyakarta, 2003)
Allah Azza Wa J alia said in Quran, “From inside a bee’s stomach it is spread off a colourful drink, which consists of medicine that may cure human diseases. (QS. 16:69). The term of “Back to Nature”, brings us to go back to nature, lets human to see alternative medicine besides the conventional medi-cine. There are some limitations of conventional antibiotic, i.e. causing bacte¬ria resistence and side effects in quite a lot cases. This is much different with “honey”, which posseses some superiorities such as easy administration, good absorption, minimal side effects and affordable price of medicine. The antibacterial activity of honey can be used as an alternative antibac-terial remedy which is more superior and has minimal side effect. In Islam, honey is a nutrition, food supplement and a medicine as well. The objective of this research was to reveal the antibacterial effect of honey against Escheri¬chia coli by relating it to the Islam knowledge and technology. The characteristic of honey that has antibacterial activity, is known as the effect of “inhibition ”. The antibacterial avtivity is related to total composition of honey, i.e. high sugar concentration, acidity and the presence of pollen. It is also influenced by a substance like lysozyme, which is more commomly known as inhibine. The antibacterial activity of honey is also related to its osmotic process.. Honey is a saturation liquid and supersaturation of sugar which was said to possess osmotic capability. Water molecule reacts strongly to sugar in honey, leaving only a little water to the microorganism ’s life. Decomposi¬tion of hidrogen peroxide increases reactive-free radical molecules that will react to bacteria and kill it. Osmotic pressure causes hidration of bacteria which hence can not survive.Allah Azza Wa Jalla berfirman dalam Al Qur’an,